Epigenetic modifications in the murine liver upon depletion of transcriptional coregulator host cell factor 1 - Shruti Kaushal; Debashruti Bhattacharya; Saran Kumar; Winship Herr; Jaspreet Kaur Dhanjal; Shilpi Minocha (BMC Genomics)
Abstract Background Transcriptional co-regulators fine-tune gene expression by modulating transcription factor activity and chromatin dynamics. HCF-1 (Host Cell Factor 1), a conserved transcriptional co-regulator, has been implicated in cell cycle progression, liver metabolism, and regeneration. Loss of hepatocyte-specific HCF-1 in mice leads to spontaneous NAFLD, which rapidly exacerbates to NASH and compromises liver regeneration. While its role in transcriptional regulation is well-established, the impact of HCF-1 on epigenetic modifications remains relatively unexplored. Methods To investigate the consequences of HCF-1 depletion, we performed histological and biochemical analyses of murine livers, assessing liver injury, lipid accumulation, and hepatocyte proliferation upon 2/3 partial hepatectomy (PH). Additionally, we conducted RNA sequencing (RNA-seq) and chromatin immunoprecipitation sequencing (ChIP-seq) for H3K4me3 and RNA polymerase II (POL2) to examine the epigenetic and transcriptional alterations associated with HCF-1 loss. Results Loss of HCF-1 results in severe liver injury, causing hallmark features of NAFLD, including steatosis, inflammation, fibrosis, and mitochondrial dysfunction. Following injury, hepatocytes typically re-enter the cell cycle to replenish lost cells. However, in the absence of HCF-1, hepatocytes fail to proliferate leading to a progressive decline in liver function. Even upon 2/3 PH, HCF-1-deficient hepatocytes remain arrested in the cell cycle, further exacerbating disease severity and preventing tissue regeneration. RNA-seq analyses revealed significant downregulation of genes involved in cell cycle progression, metabolism, and mitochondrial structure and function including those regulating oxidative phosphorylation. ChIP-seq data showed altered H3K4me3 patterns at promoter and enhancer regions of key hepatic genes. These findings indicate that HCF-1 is essential for maintaining transcriptional and epigenetic landscapes necessary for hepatocyte proliferation and regeneration. Conclusions Our study establishes HCF-1 as a critical regulator of hepatic homeostasis, with roles extending beyond transcriptional control to epigenetic regulation of liver function and repair. Loss of HCF-1 not only induces liver injury and NAFLD but also prevents hepatocyte proliferation, impairing regeneration and accelerating disease progression.